2015
DOI: 10.7747/jfes.2015.31.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Acacia senegal (L.) Wild Seedlings Growth under some Tree Manures and NPK Fertilizers in Nursery Site

Abstract: This study aimed to assess the effects of tree manures in comparison with NPK fertilizer on growth of Acacia senegal on the growth performance of Acacia senegal seedlings occurred in the following descending order: Azadirachta indica> Albizia lebbeck>Khaya senegalensis>NPK fertilizer. These results assert clearly the ameliorative and fertilizing characteristics of tree manures that can be reliably used for raising seedlings stocks in the nurseries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…This increase in collar diameter with manure application could be attributed to increased availability of nutrients through mineralization of the manure (Biederman and Harpole, 2013;Khaitov et al, 2019). Some studies had also reported similar results where there was an increase in collar diameter of Acacia senegal seedlings with manure application compared to the control (Daldoum and Hammad, 2015). The results of this study also show that seedlings treated with biochar had a lower collar diameter than the control (Table 3).…”
Section: Casuarina Seedlings Collar Diametersupporting
confidence: 77%
See 1 more Smart Citation
“…This increase in collar diameter with manure application could be attributed to increased availability of nutrients through mineralization of the manure (Biederman and Harpole, 2013;Khaitov et al, 2019). Some studies had also reported similar results where there was an increase in collar diameter of Acacia senegal seedlings with manure application compared to the control (Daldoum and Hammad, 2015). The results of this study also show that seedlings treated with biochar had a lower collar diameter than the control (Table 3).…”
Section: Casuarina Seedlings Collar Diametersupporting
confidence: 77%
“…The increase in C. equisetifolia seedling height with manure application can be attributed to increased available nitrogen with manure application. Manure used for the experiment had a narrow C/N ratio which led to net N mineralization compared to biochar which had a wider C/N ratio (Table 2) (Truong and Marschner, 2018;Daldoum and Hammad, 2015). Such increase in plant height with manure application had also been reported by Prakash et al (2014) who used seedlings of Calendula officinalis.…”
Section: Casuarina Seedlings Height (Cm)mentioning
confidence: 53%
“…A positive effect of nutrient supply on Senegalia senegal growth has been revealed in an earlier study [42]. The significant increase in total biomass was likely due, in part, to the significant increase in the net photosynthetic rate under fertilizer conditions in most families (Figure 1a).…”
Section: Discussionsupporting
confidence: 62%
“…The results of present study indicated that the used of peat soil (100%) as the medium of geronggang seedling was relatively time consuming, due to in other tree species the good quality seedling could be obtained at the shorter time, i.e of 3 -7 months [12,20,23,24]. This relatively long duration also was showed by the study of [14], which was showed that the qualified geronggang's seedling from wilding system and grown in top soil+compost medium could obtain in the age of 8 MAT.…”
Section: Resultsmentioning
confidence: 77%